2020
DOI: 10.1371/journal.pcbi.1007767
|View full text |Cite
|
Sign up to set email alerts
|

The hydrophobic effect characterises the thermodynamic signature of amyloid fibril growth

Abstract: Many proteins have the potential to aggregate into amyloid fibrils, protein polymers associated with a wide range of human disorders such as Alzheimer's and Parkinson's disease. The thermodynamic stability of amyloid fibrils, in contrast to that of folded proteins, is not well understood: the balance between entropic and enthalpic terms, including the chain entropy and the hydrophobic effect, are poorly characterised. Using a combination of theory, in vitro experiments, simulations of a coarse-grained protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 77 publications
1
39
0
Order By: Relevance
“…Consistent with this assumption, in in vitro studies -synuclein fibrils are noted to be unusually heat labile [10][11] . To maintain functional stoichiometry, the dynamic steady state level of -synuclein at the nerve terminus is coupled to efflux of non-functional fibrils through scavenging activities and influx of freshly synthesised monomers (not shown in the figure).…”
Section: Main Textmentioning
confidence: 55%
“…Consistent with this assumption, in in vitro studies -synuclein fibrils are noted to be unusually heat labile [10][11] . To maintain functional stoichiometry, the dynamic steady state level of -synuclein at the nerve terminus is coupled to efflux of non-functional fibrils through scavenging activities and influx of freshly synthesised monomers (not shown in the figure).…”
Section: Main Textmentioning
confidence: 55%
“…Previous studies have reported the importance of hydrophobicity and aromaticity in amyloid assembly and brillation. [33][34][35][36] The subdued hydrophobicity in presence of polydatin further validates its potential to be used as a prion intervening scaffold and therapeutic agent which may help in abrogating the amyloid assembly of aggregating monomers by binding to its aromatic and hydrophobic patches.…”
Section: Polydatin-induced Off-pathway Rprp Res Aggregates Exhibit Low Cross-b Content and Retain A Lower Surface Hydrophobicitymentioning
confidence: 99%
“…We set out to evaluate the performance of our method for targeted proteomics, based on simulations. For this we sought to identify the different spliceoforms of the apoptosis regulator Bcl-2 (UniProt ID: Q07817), which are potential biomarkers for cancer 23 and are likely to produce different fingerprints. While BCL-XL is an anti-apoptotic regulator, both BCL-XS and BCL-Xb are pro-apoptotic factors.…”
Section: Fingerprinting Simulation Of Protein Spliceoformsmentioning
confidence: 99%
“…Despite their simplicity, past investigations have shown that lattice models can reproduce native protein folding behavior. [19][20][21][22][23] The attachment of DNA tags to selected residues, as required to accurately model our approach, has not previously been included in lattice models. The precise effect of DNA tags on protein structure is unclear.…”
Section: Fingerprinting Simulationsmentioning
confidence: 99%